Reduction and transformation of nanomagnetite and nanomaghemite by a sulfate-reducing bacterium. (1st July 2019) - Zhou, Yuefei; Gao, Yang; Xie, Qiaoqin; Wang, Jin; Yue, Zhengbo; Wei, Lin; Yang, Yang; Li, Ling; Chen, Tianhu
Abstract: Magnetite and maghemite are important components of iron oxides that determine the magnetic properties of rocks, soils, and sediments, and are also materials with broad industrial applications. We investigated the reduction and transformation of both phases with a strain of sulfate-reducing bacteria (SRB). SRB growth resulted in 28.1% and 7.1% sulfate to acid volatile sulfur conversion in magnetite and maghemite, respectively. Transmission electron microscopy and X-ray photoelectron spectroscopy (XPS) analyses indicate that monosulfides (mackinawite and greigite) and polysulfides are the main secondary sulfides in the magnetite experiment, while the maghemite experiment also contained a high proportion of pyrite. XPS analyses indicate the reduction of Fe(III) to Fe(II) on the surface of magnetite and maghemite both by dissolved sulfides and SRB. Mössbauer spectroscopy measurements reveal the formation of superparamagnetic phases in microbial experiments, which indicates the dissolution and particle size decrease of the two minerals both by dissolved sulfides and SRB. X-ray diffraction and Mössbauer spectroscopy analyses suggest a complete transformation of nanomaghemite to nanomagnetite under the mediation of SRB through solid phase Fe(III) reduction. This transformation controls the changing and different patterns of both magnetic susceptibility and magnetic hysteresis for the two minerals. It is suggested that the structural similarity between magnetite and maghemite, and the conductivity of magnetite, constrain the unique solid phase transformation. Our findings indicate that the maghemite–magnetite solid solution is a potential natural battery for the growth of anaerobic microbes in sulfidic environments.